Um Ambiente para Sonorização Não Intrusiva de Aplicações Orientadas a Objetos - Ballista, André Luiz Costa; Price, Roberto Tom (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24453, 1996)
Marola a framework for the sonification of object oriented applications, is briefly described. Besides the generalised class structure for the creation of auditory interfaces Marola also offers a toolkit for the interactive creation of sonic classes at all levels of the framework Auditory interfaces developed with this framework may be attached to Smalltalk applications through a reflective computational mechanism, without the need of instrumenting the application classes with any sort of code.